A broken mirror? From representation to presentation of gender in Scandinavian news media - Kjeldsen Anna Karina; Schmeltz Line; Simonsen Jacob V. (Nordic Journal of Media Studies)
Across Scandinavia, one can witness a situation where gender equality has previously been at the forefront of the political and societal agenda, but where progress now seems to be slowing down. The news media is a domain where this negative development is particularly pronounced, and several studies have established that the Scandinavian news media display a more unequal gender representation than the society they supposedly mirror. In this article, we report on an ongoing cross-Scandinavian research project on news media content, where we explore not only the traditional metrics of how many men and women are in the news, but also, more importantly, how women and men are portrayed in news media content. The study demonstrates significant gender discrepancies, echoing findings from previous studies on the quantitative representation of women and men, and, more importantly, it introduces presentation as an additional qualitative metric. Consequently, we contribute with an analytical framework involving a range of qualitative parameters through which the news media industry can comprehensively evaluate gender equality within their content.